Internationale : organ of the International Working Men's Association (I.W.M.A.). No. 1 - Noja Ruiz, Higinio ; Besnard, Pierre; Rocker, Rudolf, 1873-1958 (Paris : Association internationale des travailleurs)
1938-05 SA15-009-007 28 pages 15X/1/137/1